If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x+3)+3x=-33
We move all terms to the left:
5(x+3)+3x-(-33)=0
We add all the numbers together, and all the variables
3x+5(x+3)+33=0
We multiply parentheses
3x+5x+15+33=0
We add all the numbers together, and all the variables
8x+48=0
We move all terms containing x to the left, all other terms to the right
8x=-48
x=-48/8
x=-6
| 1/2x-1/4=x/9 | | r=3r+1 | | R=9/7s+28 | | 8p=3p+29 | | 4(n+78)=-64 | | -5x=-4x=9 | | 5y-30=54-4y | | p/7-2=1 | | 8+-3t=-52 | | 17x-(7x-8)=68 | | -4(g-83)=-60 | | 28=r/3+23 | | 6(w-2)-4w=-30 | | 6c+21=99 | | 5m-3=42 | | 5t+5=40 | | 39x=10=29x-50 | | b/4+28=36 | | 3(g-52)=51 | | w/3+33=43 | | 9+2k=15 | | 2x/8+4=7 | | (4-5x)+7=5 | | 8=b+225 | | 8=b+22/5 | | 5-3xx=7 | | p+26/7=9 | | (n+1)/(2n+3)=1 | | 16=1+3r | | (6+8x)1/2=5x | | c-36/4=10 | | 7+v1.25=6=v |